2017
DOI: 10.1071/an14995
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological quality and sensory evaluation of new cured products obtained from sheep and goat meat

Abstract: The present work aims to study the effect of species and seasoning time on the physicochemical, microbiological and sensory characteristics of cured legs of sheep and goats. Three cure periods were used: two for sheep and one for goat legs. Legs of lamb were cured for 7 and 8 months whereas legs of goat were cured for 8 months only. Samples were evaluated regarding pH, water activity and indicators of food microbial quality and safety. A trained panel carried out the sensory analysis, with aroma, texture, appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 29 publications
4
11
0
Order By: Relevance
“…⁎⁎⁎ P ≤ 0.001. adhesiveness and fibers feeling (P ≤ 0.001), all texture attributes, and the least discriminating between one product and another is the acid taste, aroma intensity and marbling (P > 0.05). These results are in accordance with Tolentino et al (2016) that also found that sheep and goats cured legs were better discriminated by texture attributes. Table 4 also presents the adjusted mean ± standard error of the goats and sheep cured legs sensory attributes.…”
Section: Sensory Analysissupporting
confidence: 81%
See 4 more Smart Citations
“…⁎⁎⁎ P ≤ 0.001. adhesiveness and fibers feeling (P ≤ 0.001), all texture attributes, and the least discriminating between one product and another is the acid taste, aroma intensity and marbling (P > 0.05). These results are in accordance with Tolentino et al (2016) that also found that sheep and goats cured legs were better discriminated by texture attributes. Table 4 also presents the adjusted mean ± standard error of the goats and sheep cured legs sensory attributes.…”
Section: Sensory Analysissupporting
confidence: 81%
“…Also the a w decreased successively from the slaughter to the salting and from there to the end of ripening period with a w values significantly different between sheep and goat, 0.87 and 0.83 respectively. The values found were similar to those found by several authors: for meat cured products from different species (Paleari, Moretti, Beretta, Mentasti, & Bersani, 2003) including the goat bresaola although with an pH value higher (6.48); for smoked goat ham (Ivanovic, Nesic, Pisinov, & Pavlovic, 2016); for goat and sheep meat cured mantas (Oliveira et al, 2014); as well for sheep and goat cured legs submitted at different ripenning periods (Tolentino et al, 2016) or also for beef cecina (Molinero et al, 2008). The pH and aw values found for us showed that could be an important role in controlling the meat spoiling promoting safety and shelf life stability of the products with respect to microbial growth.…”
Section: Physicochemical Characteristicssupporting
confidence: 76%
See 3 more Smart Citations